Transforming school budgets into instructional impact: Financial efficiency in teaching and learning - Lovi Aninda; Rambat Nur Sasongko; Connie (Indonesian Journal of Educational Development (IJED), 2026)
Educational funding is increasingly expected to generate measurable instructional impact; however, many schools still struggle to translate available budgets into effective teaching and learning practices. This condition creates an urgent need for research that examines not only how much funding is provided, but how efficiently it is managed at the school level. This study aims to analyze how school budgets can be transformed into instructional impact through efficient financial management using an evaluative perspective. Employing a qualitative case study with a CIPP evaluation framework, the research was conducted at a public junior high school in Central Bengkulu, Indonesia. The population comprised school management and teachers, and participants were selected through purposive sampling to ensure information-rich data. Data were collected through semi-structured interviews, classroom observations, and document analysis using interview guides, observation protocols, and financial document checklists as research instruments. The findings reveal that instructional financial efficiency is achieved when participatory planning, disciplined implementation, reflective evaluation, and systematic follow-up operate coherently. The study offers novelty by applying the CIPP model specifically to instructional financing at the school level and providing empirical evidence linking budgets directly to classroom practices. It is recommended that schools institutionalize teacher participation in budgeting, strengthen evaluation mechanisms tied to instructional outcomes, and consistently use evaluation results to refine budgets.